Proteomic Analysis of Survival of Rhodococcus jostii RHA1 during Carbon Starvation - Patrauchan, Marianna A. (American Society for Microbiology, 2012)
Rhodococcus jostii RHA1, a catabolically diverse soil actinomycete, is highly resistant to long-term nutrient starvation. After 2 years of carbon starvation, 10% of the bacterial culture remained viable. To study the molecular basis of such resistance, we monitored the abundance of about 1,600 cytosolic proteins during a 2-week period of carbon source (benzoate) starvation. Hierarchical cluster analysis elucidated 17 major protein clusters and showed that most changes occurred during transition to stationary phase. We identified 196 proteins. A decrease in benzoate catabolic enzymes correlated with benzoate depletion, as did induction of catabolism of alternative substrates, both endogenous (lipids, carbohydrates, and proteins) and exogenous. Thus, we detected a transient 5-fold abundance increase for phthalate, phthalate ester, biphenyl, and ethyl benzene catabolic enzymes, which coincided with at least 4-fold increases in phthalate and biphenyl catabolic activities. Stationary-phase cells demonstrated an ∼250-fold increase in carbon monoxide dehydrogenase (CODH) concurrent with a 130-fold increase in CODH activity, suggesting a switch to CO or CO(2) utilization. We observed two phases of stress response: an initial response occurred during the transition to stationary phase, and a second response occurred after the cells had attained stationary phase. Although SigG synthesis was induced during starvation, a ΔsigG deletion mutant showed only minor changes in cell survival. Stationary-phase cells underwent reductive cell division. The extreme capacity of RHA1 to survive starvation does not appear to involve novel mechanisms; rather, it seems to be due to the coordinated combination of earlier-described mechanisms.